Impact of Renewable Energy use, CO2 Emissions, Oil Production and Oil Prices on Sustainable Economic Growth: ARDL Approach from Kazakhstan - Chigarkina, Olga; Suleimenova, Arailym; Turkeyeva, Kulyash; Bodaubayeva, Gulmira (International Journal of Energy Economics and Policy, 2025)
The coexistence of humanity with nature, not harming the last one is one of the dilemmas that has existed since ancient times. The environment is deteriorating every year due to damage caused by human activities. The objective of this research work is to evaluate the importance of key indicators such as renewable energy use, CO2 emissions, oil production and oil prices for sustainable economic growth using Autoregressive Distributed Lag (ARDL) model. Years cover 2000-2021 period. A worldwide literature review was conducted and hypotheses to be tested were identified. Based on a literature review, the influence of indicators on the Kazakh economy was selected and assessed. According to model results, the impact of fossil CO2 emissions per capita (tons) emissions on GDP per capita is negative in short-term and long-term terms. Renewable energy use has a positive short-term and long-term positive impact on GDP per capita. In addition to the above, crude oil production impact on GDP per capita is positive in the short and long term. In addition, the crude oil price has a positive short-term and long-term impact on GDP per capita.